Tetrandrine inhibits proliferation of colon cancer cells by BMP9/ PTEN/ PI3K/AKT signaling - Zhou, Ya (Genes Dis, 2019)
Despite advances in screening and treatment, colon cancer remains one of the leading causes of cancer-related death. Finding novel and useful drug treatment targets is also an urgent need for clinical applications. Tetrandrine (Tet) is extracted from the Chinese medicinal herbal medicine, which is a well-known calcium blocker with a variety of pharmacological activities, including anti-cancer. In this study, we recruited cell viability assay, flow cytometry analysis, cloning formation to confirm that Tet can inhibit the proliferation of SW620 cells, and induce apoptosis. Mechanically, we confirmed that Tet up-regulates the mRNA and protein level of BMP9 in SW620 cells. Over-expression BMP9 enhances the anti-cancer effects of Tet in SW620 cells, but these effects can be partly reversed by silencing BMP9. Also, Tet reduces phosphorylation of Aktl/2/3 in SW620 cells, which could be elevated by overexpressed BMP9 and impaired by silencing BMP9. Furthermore, we demonstrated that Tet reduces phosphorylated PTEN, which can be promoted by overexpressed BMP9, analogously also be attenuated through silencing BMP9. Finally, we introduced a xenograft tumor model to investigate the anti-proliferative effect of Tet, further to explore the effects of BMP9 and PTEN in SW620 cells. Our findings suggested that the anti-cancer activity of Tet in SW620 cells may be mediated partly by up-regulating BMP9, followed by inactivation PI3K/Akt through up-regulating PTEN at least.